Addressing Critical Gaps in Service Provision for First Nations Children in Canada: The Establishment and Expansion of Jordan's Principle - Alexander Ryan Levesque (McMaster University Library Press, 2018)
In 2007, the House of Commons unanimously passed a motion calling for the federal government to adopt Jordan's Principle. This child-first principle was intended to address jurisdictional disputes over the provision of services for First Nations children. The motion itself was vaguely worded-requiring no funding increases or new services for First Nations children-and allowed the federal government to implement a very narrow interpretation of Jordan's Principle. This narrowed scope applied only to on-reserve First Nations children with complex health issues and who were caught in a jurisdictional dispute. First Nations advocates then engaged in several legal challenges in order to strengthen and broaden the implementation of Jordan's Principle. In 2016 the Canadian Human Rights Tribunal (CHRT) ordered the federal government to immediately end discrimination against First Nations children and implement Jordan's Principle in full. Through subsequent compliance orders the CHRT increased the scope of Jordan's Principle to include all First Nations children living on or off a reserve-regardless of the presence of medical conditions or a jurisdictional dispute. Jordan's Principle now has the opportunity to address critical service gaps and increase the well-being of First Nations children throughout Canada. However, it remains to be seen if Canada will fully comply with the CHRT's order, and how the federal government will work with the provinces to implement Jordan's Principle.